2022
DOI: 10.1093/oncolo/oyac218
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Race/Ethnicity, Language, and Enrollment on Cancer Research Studies

Abstract: Purpose The objective of this study was to determine whether differences in patients’ race/ethnicity, preferred language, and other factors were associated with patient enrollment in oncology research studies. Patients and Methods We conducted a retrospective cross-sectional analysis of all adults (>18 and ≤90) seen at a large, metropolitan cancer center from 2005 to 2015, examining if enrollment to a research study, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…2006 to 2016 (N = 19,453) found that patients with a preferred language other than English were over 50% less likely to participate in a CT. 46 Similarly, a retrospective cross-sectional analysis of patients seen at an NCI-designated comprehensive cancer center between 200-2015 (N = 233,604) found that patients with a non-English language preference had a 45% reduced odds of enrollment in a research study in adjusted analyses (OR, 0.55; 95% CI, 0.53-0.58). 47 Disparities in trial access for this population are further heightened by the requirement of English fluency as an inclusion criterion. A review of 10,000 CT protocols registered with Clin-icalTrials.gov found that the proportion of CTs with an English fluency requirement has increased from 1.7% of trials before 2000 to 9% of trials after 2010.…”
Section: Univariable and Multivariable Regressionmentioning
confidence: 99%
“…2006 to 2016 (N = 19,453) found that patients with a preferred language other than English were over 50% less likely to participate in a CT. 46 Similarly, a retrospective cross-sectional analysis of patients seen at an NCI-designated comprehensive cancer center between 200-2015 (N = 233,604) found that patients with a non-English language preference had a 45% reduced odds of enrollment in a research study in adjusted analyses (OR, 0.55; 95% CI, 0.53-0.58). 47 Disparities in trial access for this population are further heightened by the requirement of English fluency as an inclusion criterion. A review of 10,000 CT protocols registered with Clin-icalTrials.gov found that the proportion of CTs with an English fluency requirement has increased from 1.7% of trials before 2000 to 9% of trials after 2010.…”
Section: Univariable and Multivariable Regressionmentioning
confidence: 99%
“…This can inadvertently deprive underprivileged or marginalised sectors of society from participation in clinical research 14. Patients of minority ethnic background have been shown to be less likely to be enrolled in research studies 15 16. Greater diversity can improve generalisability of trial results by making a trial population more representative of the general population.…”
Section: Introductionmentioning
confidence: 99%